A Path towards Technology Driven Education: Attitude of Teachers towards Innovative Teaching Practices - Mathews, Soney; Jassel, Jagdeep Singh (2015)
In today's Digital Age, teaching and learning is becoming dynamic. Technology is used to create unique teaching and learning experiences. Universities and campuses are moving towards technology adopted teaching and learning practices. In the global perspective, this shift is considered as an innovative practice in education. Even though most of the teachers are shifting themselves to technology adopted teaching, there is a bit concern of adopting technology. Technology driven education can lead quality in education. Due to technology adopted teaching practices, teachers' role is shifting from the information provider to a mentor or facilitator. This empirical research study is done to understand the attitude of teachers towards innovative teaching practices.